2017
DOI: 10.15403/jgld.2014.1121.262.gus
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Adenocarcinoma with Enteroblastic Differentiation Arising in Ectopic Gastric Mucosa in the Cervical Esophagus: a Case Report and Literature Review

Abstract: Background: Adenocarcinoma with enteroblastic differentiation is a subtype of alpha-fetoprotein (AFP) producing adenocarcinoma. This type of tumor is associated with a poor prognosis and is prone to metastasize. Esophageal adenocarcinoma with enteroblastic differentiation is extremely rare.Case presentation: The patient was a 65-year-old woman who was referred to our hospital with dysphagia. Endoscopic examination revealed an elevated lesion 20mm in diameter at 17cm from the upper incisors. Endoscopic submucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…APA is a rare kind of malignant tumor, which could originate from various organs, such as the lung, ovary, kidney, esophagus, stomach, small intestine, colorectal, and appendix (3,10,(14)(15)(16)(17)(18). The present study focused on the clinicopathological features of APA-GI via a retrospective analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APA is a rare kind of malignant tumor, which could originate from various organs, such as the lung, ovary, kidney, esophagus, stomach, small intestine, colorectal, and appendix (3,10,(14)(15)(16)(17)(18). The present study focused on the clinicopathological features of APA-GI via a retrospective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The serum AFP in APA patients is increased (>20ng/ml) and markers representing embryonic stem cells and hepatocellular carcinoma in tumor tissues, such as AFP protein, glypican-3, Sal-like protein-4, and/or hepatocyte antigen-1, are positive (7,8). APA originated from the gastrointestinal tract (APA-GI) was reported to have some common clinical characteristics, such as early multi-organ metastasis, multidrug resistance, rapidly worsen after diagnosis, and much inferior prognosis than common adenocarcinoma of the gastrointestinal tract (CA-GI) (5,6,(9)(10)(11). Although the previous studies of APA-GI usually only included APA-GC or APA-CRC (3,12), we found APA-GI could also originate from the whole GI tract, including the esophagus, small intestinal, and appendix.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30 case reports of adenocarcinoma occurring from ectopic gastric mucosa of the esophagus have been reported since 1950 (8), but our search of the literature revealed no reported case of squamous cell carcinoma neighboring and invading ectopic gastric mucosa. As another rare case, there are a report to undergo ESD for esophageal adenocarcinoma with enteroblastic differentiation arising from ectopic gastric mucosa in the esophagus (9). In our case, the squamous cell carcinoma invaded into the submucosal layer under the ectopic gastric mucosa.…”
Section: Discussionmentioning
confidence: 65%
“…In 8 patients who underwent magnifying endoscopy, the findings were irregular microvessels and/or irregular microstructures, similar to those of early gastric cancers 3, 4, 6, 7, 8, 9, 10. Histopathologically, almost all cases of adenocarcinoma were differentiated adenocarcinomas.…”
mentioning
confidence: 75%
“…Of those, including this case, endoscopic treatment was administered in only 11 cases (Table 1). 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 Most of those lesions were elevated, and nearly half had a reddish color noted on endoscopic examination. In 8 patients who underwent magnifying endoscopy, the findings were irregular microvessels and/or irregular microstructures, similar to those of early gastric cancers 3, 4, 6, 7, 8, 9, 10.…”
mentioning
confidence: 99%